A green perspective on simultaneous HPLC and UV spectrophotometric estimation of Udenafil and Dapoxetine hydrochloride in pharmaceutical formulations - Sandesh Bherje; Mital Patel (Green Analytical Chemistry, 2024)
Clinical research has affirmed that the combination of Udenafil and Dapoxetine hydrochloride yields greater improvement in erectile dysfunction compared to the use of individual medications. There is a requirement of precise quantitative method for accurate determination of Udenafil and Dapoxetine when taken together. Consequently, our interest lies in developing and validating analytical methods for the simultaneous estimation of Udenafil and Dapoxetine - Various strategies, such as UV spectrophotometric approaches and an innovative, straightforward, accurate, sensitive, and robust High-Performance Liquid Chromatography (HPLC) procedure, have been explored. An Isocratic HPLC approach was employed using reversed-phase CHEMSIL ODS C18 column (4.6 mm x 250 mm, 5 µm) as a stationary phase and detection wavelength (λ max) 230 nm for the two analytes in the chromatographic column. The mobile phase comprised of (70:30, v/v) mixture of Acetonitrile and 10 mM Ammonium formate buffer having pH 5, adjusted with formic acid. The elution was carried out at a constant flow rate of 1 mL/min. The UV simultaneous equation technique estimated the medicine's quantities and derived a simultaneous equation for DAP and UDN using 2 wavelengths, 230 nm and 298 nm. Furthermore, the two advanced methods underwent rigorous statistical validation, guided by the valuable ICH Q2R1 guidelines, affirming their effectiveness as a successful analytical tool for the concurrent analysis of both tablets in bulk and the synthetic mixture fabricated in the laboratory. To assess the environmental impact of contemporary UV spectrophotometric and HPLC techniques, the Green Analytical Greenness Metric (AGREE) software and the Green Analytical System Index (GAPI) were employed to evaluate the greenness profile. This examination confirmed the method's environmental friendliness concerning solvent usage, chemical ingredients, energy consumption, and waste production. The developed UV method is more sustainable and greener compare to HPLC method for simultaneous estimation of compound, which can be utilised by industry for quantification of each individual drug in their combination products.